The phenomenon of photoinhibition of photosynthesis and its importance in reforestation - Alves, Pedro Luís Da C. A. [UNESP]; Magalhães, Antônio C. N.; Barja, Paulo Roxo (My University, 2002)
Photoinhibition, defined as the inhibition of photosynthesis caused by excessive radiance, affects field production to a great extent. This phenomenon is particularly relevant in reforestation practices, when one deals with forests of rapid growth such as Eucalyptus. The imposition of additional stress factors during exposure to high radiance increases the potential for photoinhibitory effects, so the inhibition of photosynthesis indicates that the plant is submitted to stressful conditions. Photoinhibition can be reversible, playing a protective role for the photosynthetic systems, but it can also reflect damage that has already occurred in the photosynthetic apparatus, being irreversible in this case. In this review, we present the physiological and molecular mechanisms of photoinhibition and discuss the interaction between light and other stress factors and its effects on plants destined for reforestation. In addition, the present work analyzes some of the features and strategies that help plants avoid or restrict the occurrence of photoinhibition. For instance, pigments and enzymes which naturally occur in plants can prevent photoinhibition, while preadaptation to nonideal conditions can enhance tolerance to a certain stress factor. Most of these morphological, metabolic, and biochemical mechanisms of defense are related to the dissipation of excessive energy such as heat. Understanding these mechanisms can help improve cultivation procedures, avoid the plants' death, and increase productivity in the field.
Keywords: Eucalyptus